2016
DOI: 10.22159/ijpps.2016v8i11.14175
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant Activity and Gc-MS Analysis of the Ethanolic Extracts of Terminalia Bellerica Roxb (Baheda)

Abstract: Objective: To investigate the antioxidant activity of ethanolic extract of Terminalia bellerica fruit pulp (TBFP), seed (TBS) and bark (TBB), and identification of phytochemical constituents of said extracts. Methods:The antioxidant potential of T. bellerica (TB) parts was evaluated by free radical scavenging activity (FRSA), superoxide anion radical scavenging activity (SARSA), hydroxyl radical scavenging activity (HRSA) and compared with reference standard quercetin. Lipid peroxidation (LPO), ferric thiocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In fact, at high dose, they were attributed to direct toxic effect and induced cells to death. It is evident from the extent of activity that T. bellerica contains hepatoprotective principles not only in fruits as reported earlier [18,19], but the leaves and bark also contain various bioactive principles which may responsible for the hepatoprotective potential of T. bellerica [7]. Thus, determination of percentage cell viability of plant extracts is a biochemical parameter which indicates towards the potential of medicinal plants for their antioxidant, anti-inflammatory, anticancer and hepatoprotective activities.…”
Section: : Carbon Tetrachloridementioning
confidence: 65%
See 2 more Smart Citations
“…In fact, at high dose, they were attributed to direct toxic effect and induced cells to death. It is evident from the extent of activity that T. bellerica contains hepatoprotective principles not only in fruits as reported earlier [18,19], but the leaves and bark also contain various bioactive principles which may responsible for the hepatoprotective potential of T. bellerica [7]. Thus, determination of percentage cell viability of plant extracts is a biochemical parameter which indicates towards the potential of medicinal plants for their antioxidant, anti-inflammatory, anticancer and hepatoprotective activities.…”
Section: : Carbon Tetrachloridementioning
confidence: 65%
“…bellerica contains a diverse set of vital phytoconstituents like gallic acid, ethyl galate, quinic acid, octadecanoic acid, glucopyranose, sitosterols etc [7]. Polyphenolic compounds in T. bellerica had dual effects on cells and modulated cell proliferation in a dosedependent manner.…”
Section: : Carbon Tetrachloridementioning
confidence: 99%
See 1 more Smart Citation
“…It is an integral part of ancient formulation, Triphala which is used for a variety of ailments in Ayurveda. GC-MS analysis revealed that TB contains various polyphenolic and other bioactive compounds such as gallic acid, quinic acid (chlorogenic acid), ethyl galate, 9,12 octadecadienoic acid, glucopyranose, sitosterol, protein, tannins, galactose, glucose, mannitol, fructose, ramnose etc [10]. Antioxidant activities increase proportionally with the polyphenol content, primarily because of their redox properties.…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography mass spectrometry (GC-MS) analysis revealed that T. bellerica contains various polyphenolic and other bioactive compounds such as gallic acid, quinic acid (chlorogenic acid), ethyl galate, 9,12 octadecadienoic acid, glucopyranose, sitosterol, protein, tannins, galactose, glucose, mannitol, fructose, ramnose etc. (Gupta et al, 2016). Antioxidant activities increase proportionally with the phenolic content, primarily because of their redox properties (Gupta et al, 2015(Gupta et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%